Thermal Effect on the Bioconvection Dynamics of Gravitactic Microorganisms in a Rectangular Cavity - Rubén Mil-Martínez; René O. Vargas; Juan P. Escandón; Ildebrando Pérez-Reyes; Marcos Turcio; Aldo Gómez-López; Francisco López-Serrano (Fluids, 2022)
In this work, the dynamics of the bioconvection process of gravitactic microorganisms enclosed in a rectangular cavity, is analyzed. The dimensionless cell and energy conservation equations are coupled with the vorticity-stream function formulation. Then, the effects of the bioconvection Rayleigh number and the heating source on the dynamics of microorganisms are discussed. The results based in streamlines, concentration and temperature contours are obtained through numerical simulations considering eight different configurations of symmetrical and asymmetrical heat sources. It is concluded that microorganisms accumulate in the warmer regions and swim through the cooler regions to reach the surface. They form cells for each heat source, but at high concentrations, they form a single stable cell. The results presented here can be applied to control and to understand the dynamics of microorganisms with discrete heat sources.